Effects of three protocols of hamstring muscle stretching and paravertebral lumbar - Juliana Moesch; Juliana Schmatz Mallmann; Flávia Tomé; Lizyana Vieira; Rodolfo Tozeto Ciqueleiro; Gladson Ricardo Flor Bertolini
Introduction the muscle stretching is widely used to gain extensibility and flexibility, it is important to know the duration of these effects, after return to usual activity level. Thus, the aim of this study was to analyze the effect of three protocols of hamstring and paravertebral lumbar muscles stretching, and joint flexibility and muscle extensibility after six weeks. Methods participants were 40 volunteers, with limited hamstring extensibility, randomized into three groups: active stretching static (n = 14), proprioceptive neuromuscular facilitation (n = 14) and kinesiostretching (n = 12). The protocol was divided into 3 stages: the 1st control (six weeks), the 2nd application of stretch (six weeks) and the 3rd follow-up (eight weeks). The project was approved by the Ethics Committee on Human Research Unioeste, under protocol number 25536/2008. Four evaluations were conducted with board coupled to a system and goniometry and Well´s bench, distributed at the beginning and end of each step. Data were analyzed with repeated measures ANOVA, and one-way, with a significance level of 5%. Results there was no significant difference for the three groups in the control stage. There were significant differences in the three protocols in the stage of stretching. After follow-up stage, there was significant difference in the ratings to the board goniometry, and there was no difference in the Well's Bench. Conclusion the three techniques promoted significant gain in extensibility and flexibility, extensibility was not maintained after the follow-up stage, and the flexibility of the posterior chain continued gains.